The Effect of Leadership Style and Compensation on the Work Performance of Merangin District Office Employees, Jambi: The Role of Work Motivation - Nalim Nalim; Siswoyo Haryono; Murniady Muchran (Journal of Governance and Public Policy, 2020)
The purpose of this study was to examine the effect of leadership style and compensation on work motivation and its implications for the performance of the staff of the Merangin Regency Secretariat, Jambi, Indonesia. Research on 245 respondents from the Merangin Regency Secretariat staff, Jambi, Indonesia. The research method uses descriptive research and survey methods. The analysis model uses SEM (Structural Equation Modeling) analysis. The results showed: (1) There was a positive and significant influence of leadership style on work motivation, (2) There was a positive and significant effect of compensation on work motivation, (3) There was a positive and significant influence of leadership style on employee performance. (4) There is no effect of compensation on employee performance, (5) There is a positive and significant effect of work motivation on employee performance. From the results of the analysis of direct and indirect effects, motivation in this study is an intervening variable. The work motivation variable is intervening, especially for the compensation variable. It is recommended to the Merangin Regency Secretariat, Jambi, to improve employee performance, it is necessary to pay attention to the variables of leadership style, compensation, and work motivation.